Anterograde and Retrograde Amnesia following Bitemporal Infarction - A. Schnider; M. Regard; T. Landis (Behavioural Neurology)
A patient suffered very severe anterograde and retrograde amnesia following infarction of both medial temporal lobes (hippocampus and adjacent cortex) and the left inferior temporo-occipital area. The temporal stem and the amygdala were intact; these structures do not appear to be critical for new learning in humans. Extension of the left-sided infarct into the inferior temporo-occipital lobe, an area critically involved in visual processing, appears to be responsible for our patient's loss of remote memories.